A Summary of the 5th Campaign of the French Archaeological Mission at Qasr Shemamok (Kurdistan, Iraq), 21 September–19 October, 2016 - Masetti-Rouault, Maria Grazia (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
The French Archaeological mission at Qasr Shemamok, directed by M. G. Masetti-Rouault (École Pratique des Hautes Études, Sorbonne University, Paris) and by O. Rouault (Professor Emeritus, Lyons 2 University), started the fifth campaign of excavation on the site on 22 September, 2016, and continued to work until 16 October. The excavations we have carried out since 2011 at Qasr Shemamok, the ancient Assyrian city of Kilizu, have already allowed us to understand better the stratigraphy of the main ‘tell’, the Citadel, and to compare this sequence, from a chronological and cultural point of view, with different periods of the history of this region (Masetti-Rouault and Rouault 2014, 2015). Kilizu is well known in particular for its Assyrian levels (Figure 1). In area A, we have discovered the wall encircling the Citadel and the mudbrick terrace supporting it, as well as a backed brick path rising towards its summit, built during the reign of the Assyrian king Sennacherib (705-681 BC). In area B, we have identified the remains of a palace belonging to the Middle-Assyrian period, built by king Adad-nirari I (1308-1275 BC).